Couple Forgiveness and its Moderating Role in the Intergenerational Transmission of Veterans' Posttraumatic Stress Symptoms. (18th November 2016) - Zhou, Xiao; Levin, Yafit; Stein, Jacob Y.; Zerach, Gadi; Solomon, Zahava
Abstract : This study examined the moderating effect couple forgiveness (as perceived by the wives/mothers) may have on the intergenerational transmission of posttraumatic stress symptoms (PTSS) among families of combat veterans and former prisoners of war (ex‐POWs). The sample included 123 (79 ex‐POWs and 44 control combatants) Israeli father–mother–adult offspring triads. Self‐report measures were administered at 2008 to veterans, at 2010–2011 to wives, and at 2013–2014 to offspring. The findings indicated that ex‐POWs' PTSS were positively related to their offspring's PTSS, while couple forgiveness buffered this effect, particularly, and detrimentally, when couple forgiveness was low. These findings imply that apprehending the quality of the forgiving atmosphere within the marital relationship may be important for understanding the apparatus of intergenerational transmissions of trauma.